1991
DOI: 10.1007/bf00041218
|View full text |Cite
|
Sign up to set email alerts
|

On the encounter of an acoustic shear pulse with a phase boundary in an elastic material: energy and dissipation

Abstract: The fully dynamical motion of a phase boundary is examined for a specific class of elastic materials whose stress-strain relation in simple shear is nonmonotone. Previous work has shown that a preexisting stationary phase boundary in such a material can be set in motion by a finite amplitude shear pulse and that an infinity of solutions is possible according to the present theory. In this work, these solutions are examined in detail from the perspective of energy and dissipation. It is shown that there exists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Energetic considerations in both a quasi-static and fully dynamical sense have recently received a great deal of study with a view toward a full or partial resolution to the uniqueness issue. These results will be presented in a subsequent communication which extends the results presented here [36].…”
Section: Introductionsupporting
confidence: 69%
“…Energetic considerations in both a quasi-static and fully dynamical sense have recently received a great deal of study with a view toward a full or partial resolution to the uniqueness issue. These results will be presented in a subsequent communication which extends the results presented here [36].…”
Section: Introductionsupporting
confidence: 69%
“…Among such selection criteria, perhaps the two that are most often encountered in applications are the "viscosity-capillarity condition" studied by Shearer [10,11], Slemrod [12,13], Truskinovsky [14,15], and others, and variants of the "entropy rate admissibility criterion" proposed by Dafermos [16,17] and investigated in connection with phase transitions by Hattori [18,19], James [20], and Pence [21], For the trilinear elastic bar, the relation between a selection criterion of the viscosity-capillarity type and the kinetics of phase transitions was recently explored in [22], where it was shown that imposing this selection criterion is equivalent to the prescription of a kinetic relation / = (p{s) with a particular choice of (p . In the present paper, we show-again for the trilinear material-that the "entropy rate shock admissibility criterion" stated by Dafermos in [17], if suitably modified, is also equivalent to a kinetic relation of the form f = (p(s).…”
mentioning
confidence: 99%
“…The only work of which we are aware that is related to the specific problem under discussion here is that of Pence [4,5]. In [4], Pence studies the reflection and transmission of an acoustic shear wave from an initially stationary phase boundary in an elastic solid. The analysis in [5] is concerned with the structure of the fields in two elastic bars, one of which (the impactor) is composed of a single-phase material, while the other (the target) is made of a material capable of sustaining a phase transformation.…”
mentioning
confidence: 99%